2-(4-{3-[1-(3-Bromopropyl)-3,3-dimethyl-2,3-dihydro-1H-indol-2-ylidene]prop-1-enyl}-3-cyano-5,5-dimethyl-2,5-dihydrofuran-2-ylidene)malononitrile - Gainsford, Graeme J. (International Union of Crystallography, 2009)
The backbone of the title molecule, C(26)H(25)BrN(4)O, is approximately planar: the dihedral angle between the planes of the indoline ring system and the furan ring is 7.68 (14)°. In the crystal, layers lying parallel to (10[Image: see text]) occur, with the molecules interacting via weak C—H⋯N(cyano) and C—H⋯Br bonds and short N(cyano)⋯Br contacts [3.345 (4) Å].